Local governance quality and law compliance: The case of Mozambican firms - Hanna Berkel; Christian Estmann; John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using panel data of manufacturing enterprises in Mozambique between 2012 and 2017, we investigate how changes in perceived quality of governance are related to firms' law compliance. Controlling for firm-level unobserved heterogeneity, we look at three aspects of governance and their components: transparency, security, and infrastructure. We examine which of these have the potential to alter firm compliance behaviour. We find that enterprises' perceptions of transparency are key to law abidance. In particular, higher predictability of changes in the law, better access to legal documents, and regular meetings with state officials improve firm compliance rates. Thus, we confirm results showing that more political participation and government openness increase compliance with regulations, even in a non-democratic context. Additionally, we test whether political legitimacy acts as a mediator or a moderator in this governance-compliance relationship, but find no clear evidence of this being the case. However, we do confirm that legitimacy has an independent effect on firms' compliance with regulations in the context of Mozambique.
Keywords: D22; D23; K22; P16; 330; governance; transparency; law compliance; firms